Combined optimization of counteracting enemy amphibious operations in computer modeling - Maksymov, Maksym; Grishyn, Maksym; Neizhpapa, Oleksii (Technology audit and production reserves, 2026)
The object of research is an integrated coastal defense system using mine barriers and artillery batteries. The research was conducted for a typical landing force and uniform mining within the fairway. Among the most challenging issues are accounting for heterogeneous weapons and uncertainties in the combat environment. Another challenge is choosing between the speed of completing the operation and the cost of resources. The paper presents a combined model for countering amphibious assaults, which combines the effects of sea mine barriers and artillery fire in a single scale of relative explosive effectiveness. This allows for the optimization of resource and time expenditure. Additionally, robustness to disturbances due to the loss of mines and guns (Δm, Δg) is taken into account. The research employs: standardization of ammunition nomenclature, Markov model of shelling, probabilistic model of detonation, and two-criterion optimization. The unified model of combined optimization (ρ, G) in a common metric was developed. The operation was simulated in different modes. Robust corrections were introduced to the effective number of mines and guns in case of disturbances. For the practical selection of parameters, the ε-constraint method was applied, and tactical modes of use were outlined. The results of modelling the response time of the operation Ttot and resource costs S were obtained. Ttot depends more on G and ρ (minimum 26 minutes) than on S, which has a dominant influence to a greater extent than ρ (minimum 80 tons). This is due to the fact that as G increases, the operation time is reduced due to parallelism. Meanwhile, an increase in ρ will lead to a high probability of disruption, reducing the need for shells. Accordingly, the proposed model enables rapid selection of parameters to meet prescribed time thresholds and risks of enemy breakthrough.